The Practice of Marrying an Uncle's Daughter (Boru Tulang) in the Simalungun Islamic Community in Tinokkah Village, Sipispis Sub-District Perspective of the Shafi'i School - Jainul Ilham Saragih; Ibnu Radwan Siddik Turnip (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to examine how the practice of marrying an uncle's daughter (boru tulang) in the Simalungun Islamic community in Tinokkah Village, Sipispis District, what are the factors causing the practice of marrying an uncle's daughter, and how the Shafi'i School's perspective on the practice of marrying an uncle's daughter is still carried out by the Muslim community in the village. This research is an empirical legal research, with qualitative data analysis methods. Primary data sources were obtained from interviews with Muslim communities who practiced marrying uncles' children, traditional leaders, and the author's observations. The results showed that there are still some Simalungun Muslim communities who practice marrying with uncles' daughters (boru tulang) for the reason of wanting to further strengthen family relationships, filial piety to parents, and keep family property from going out of kinship. In the perspective of the Shafi'i School, marriage with close relatives, such as marrying with uncles' daughters (boru tulang) in the Simalungun Muslim community, is not recommended even the law is makruh because it is feared that there will be negative impacts on children. However, some people feel a positive influence in realizing family resilience, through marriage with uncle's children.